Dashboards to reduce inappropriate prescribing of metformin and aspirin: A quality assurance programme in a primary care sentinel network. Issue 6 (December 2021) - de Lusignan, Simon; Hinton, William; Seidu, Samuel; Mathew, Mekha; Feher, Michael D.; Munro, Neil; Joy, Mark; Carinci, Fabrizio; Hobbs, F.D. Richard; Khunti, Kamlesh
Highlights: 'Do-Not-Do' recommendations were introduced in the UK to reduce inappropriate prescribing. We piloted two dashboards to flag inappropriate prescribing of metformin and aspirin. At baseline, most metformin prescriptions were appropriate; only a fifth were for aspirin. Use of the dashboard reduced inappropriate prescribing of aspirin. It was feasible to use a dashboard to flag inappropriate prescribing. Abstract: Aims: To pilot two dashboards to monitor prescribing of metformin and aspirin according to the National Institute for Health and Care Excellence (NICE) 'Do-Not-Do' recommendations. Methods: This quality assurance programme was conducted in twelve general practices of the Oxford-Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) network. We developed dashboards to flag inappropriate prescribing of metformin and aspirin to people with type 2 diabetes mellitus (T2DM). In Phase 1, six practices (Group A) received a dashboard flagging suboptimal metformin prescriptions in people with reduced renal function. The other six practices (Group B) were controls. In Phase 2, Group B were provided a dashboard to flag inappropriate aspirin prescribing and Group A were controls. We used logistic regression to explore associations between dashboard exposure and inappropriate prescribing. Results: The cohort comprised 5644 individuals (Group A, n = 2656; Group B, n = 2988). Half (51.6%, n = 2991) were prescribed metformin of which 15 (0.5%) were inappropriate (Group A, n = 10; Group B, n = 5). A fifth (17.6%, n = 986) were prescribed aspirin of which 828 (84.0%) were inappropriate. During Phase 1, metformin was stopped in 50% (n = 5) of people in Group A, compared with 20% (n = 1) in the control group (Group B); in Phase 2, the odds ratio of inappropriate aspirin prescribing was significantly lower in practices that received the dashboard versus control (0.44, 95%CI 0.27−0.72). Conclusions: It was feasible to use a dashboard to flag inappropriate prescribing. Whilst underpowered to report a change in metformin, we demonstrated a reduction in inappropriate aspirin prescribing.